PENGARUH MEDIA DIGITAL DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH - Ahmad Baidhowi; Saadah, Lailatus (Universitas KH. Mukhtar Syafaat, 2026)
Digital media often comes to mind in today's modern-day educators, so changes are needed in the learning process in order to attract the sympathy of students and increase the enthusiasm for learning in difficult subjects, especially Arabic. Madrasah students still find it difficult to understand and understand foreign languages, especially Arabic, so many students ignore this, for problems that often arise, the author provides ideas related to social media such as audio visuals that are suitable for students in madrasas with the aim that students take part in carrying out a more flexible learning process and expect more optimal results. The researcher conducted a research at Madrasah ibtidaiyah miftahussa'adah Tangerang City on September 15, 2025 in grade 4 with an approach method that uses quantitative by involving a control class and an experimental class so as to obtain a population of 80 students and a sample of 26 students who were given interviews, observations, pretests and posttests then obtained results of 3,578 < 4,121 which stated that the hypothesis was accepted while explaining that digital media can affect students in Arabic language lessons so that it can be concluded that involving digital media in Arabic language learning can significantly affect students.